Penggunaan Media Tanam dan Aplikasi Dosis Pupuk Petroganik yang Berbeda terhadap Pertumbuhan dan Produksi Pakcoy (Brassica Rapa L.) - Dos Santos, Erminia Pereira (Savana Cendana, 2023)
This study aims to investigate the growth and production of pakcoy (Brassica rapa L.) with different treatments in terms of the composition of the growing medium and the dosage of petroganic fertilizers. The research was conducted at the Independent Farmers Group in Leosama Village, Kakuluk Mesak District, from September to November 2022. The method used was a Completely Randomized Trial Design with a factorial pattern consisting of two factors. The first factor is the composition of the planting medium, including three variations: T1 (Sand:Compost:Soil in the ratio 2:1:1), T2 (Sand:Compost:Soil in the ratio 1:2:1), and T3 (Sand:Compost: Soil in the ratio 1:1:2). The second factor was the dose of fertilizer, consisting of three variations: P1 (4 grams of petroganic fertilizer), P2 (8 grams of petroganic fertilizer), and P3 (12 grams of petroganic fertilizer). Thus, there were a total of nine treatment combinations: TIPI, T1P2, T1P3, T2P1, T2P2, T2P3, T3P1, T3P2, and T3P3. Each treatment combination was repeated three times, resulting in a total of 27 treatments. Further analysis was carried out using the Least Significant Difference (LSD) test. The results showed that the combination treatment of Sand:Compost:Soil (1:2:1) planting medium with a dose of 12 grams of petroganic fertilizer per polybag (T2P3) gave the most optimal growth and production results for pakcoy (Brassica rapa L.) from all parameters measured. These parameters include plant height, number of leaves, fresh and dry weight of leaves, as well as fresh and dry weight of roots.